Cholera in India: an analysis of reports, 1997-2006 - S Kanungo; BK Sah; AL Lopez; JS Sung; AM Paisley; D Sur; JD Clemens; G Balakrish Nair (The World Health Organization, 2010)
OBJECTIVE: To more accurately define the annual incidence of cholera in India, believed to be higher than reported to the World Health Organization (WHO). METHODS: We searched the biomedical literature to extract data on the cases of cholera reported in India from 1997 to 2006 and compared the numbers found to those reported annually to WHO over the same period. The latter were obtained from WHO's annual summaries of reported cholera cases and National health profile 2006, published by India's Central Bureau of Health Intelligence. FINDINGS: Of India's 35 states or union territories, 21 reported cholera cases during at least one year between 1997 and 2006. The state of West Bengal reported cases during all 10 years, while the state of Maharashtra and the union territory of Delhi reported cases during nine, and Orissa during seven. There were 68 outbreaks in 18 states, and 222 038 cases were detected overall. This figure is about six times higher than the number reported to WHO (37 783) over the same period. The states of Orissa, West Bengal, Andaman and Nicobar Islands, Assam and Chhattisgarh accounted for 91% of all outbreak-related cases. CONCLUSION: The reporting of cholera cases in India is incomplete and the methods used to keep statistics on cholera incidence are inadequate. Although the data are sparse and heterogeneous, cholera notification in India is highly deficient.